2015
DOI: 10.1002/pmh.1311
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy group-treatment for non-responsive patients with personality disorders: An exploratory study

Abstract: Patients with personality disorders who did not respond to previous outpatient treatment are among the most challenging patients to treat and are often referred to specialized settings. Acceptance and commitment therapy (ACT) is an innovative therapy that has shown effectiveness in treatment-resistant cases with chronic or recurrent depression with or without co-morbid personality disorders. The central role that ACT accords to positive values and experiential avoidance may enhance treatment responsivity in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
(40 reference statements)
2
16
0
Order By: Relevance
“…The AAQ‐II seemed an interesting measure because of its possible link between the unique experiential situation in art therapy and the concept of experiential acceptance (vs. avoidance). Experiential avoidance is considered to play a central role in the course and development of psychopathology, including PDs …”
Section: Study 2: Scale Reliability and Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…The AAQ‐II seemed an interesting measure because of its possible link between the unique experiential situation in art therapy and the concept of experiential acceptance (vs. avoidance). Experiential avoidance is considered to play a central role in the course and development of psychopathology, including PDs …”
Section: Study 2: Scale Reliability and Validitymentioning
confidence: 99%
“…The few available diagnostic scales in art therapy, such as the Diagnostic Drawing Series or the Art‐based Intervention Self‐report Questionnaire on the art‐making experience, are assessment tools and not specifically suited to measure the effects of art therapy treatment. In general, there is need for further evaluating treatment approaches for patients with PDs . To do so for art therapy, what it is needed are specific scales for monitoring and measuring the contribution of art therapy in multidisciplinary programmes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chakhssi et al (20) reported small-to-moderate decreases in general psychopathology and pathological personality traits by both acceptance and commitment therapy and CBT for patients with personality disorders who had not responded to outpatient treatment. In a case-control study, Bales et al (21, 22) found improvement after mentalization-based therapy on several measures in a cohort study of treatment-resistant patients with borderline personality disorder and comorbid conditions, the latter including other personality disorders, anxiety disorders, mood disorders, eating disorders, and substance abuse disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated admission and long‐term stays reduce the opportunity for the individual to engage in value driven activities to move towards ‘a life worth living’, thus maintaining or increasing risk, leading to the vicious cycle of repeated admissions and further reduced opportunities. Several evidence based third wave CBT therapies promote the development of skills for living a value driven life including DBT and Acceptance Commitment Therapy (ACT) (Powers, Zum Vörde Sive Vörding, & Emmelkamp, ; Chakhssi, Janssen, Pol, van Dreumel, & Westerhof, ). Finally, one needs to look at the evidence from the recovery model (Jacobson, & Greenley,).…”
mentioning
confidence: 99%